2020
DOI: 10.1002/jmv.26487
|View full text |Cite
|
Sign up to set email alerts
|

Presenting the characteristics, smoking versus diabetes, and outcome among patients hospitalized with COVID‐19

Abstract: Methods We designed a cross‐sectional, observational follow‐up for 284 COVID‐19 patients involving healthy patients, smokers, diabetics, and diabetic plus smokers recruited from May 1, 2020 to June 25, 2020. The clinical features, severity, duration, and outcome of the disease were analyzed. Results Of 284 COVID‐19 patients, the median age was 48 years (range, 18–80), and 33.80% were female. Common symptoms included fever (85.56%), shortness of breath (49.65%), cough (45.42%), and headache (40.86%). Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…A cross-sectional, observational follow-up for 284 COVID-19 infected persons indicated that multiple comorbidities are closely related to the severity of COVID-19 disease progression and the higher mortality rate was seen in smokers as compared with healthy patients [29]. A study on 10,713 COVID-19 patients in Espírito Santo State, Brazil, reported that older age, male gender, Asian, indigenous or unknown race, comorbidities like smoking, kidney disease, obesity, pulmonary disease, diabetes, and cardiovascular disease, as well as fever and shortness of breath, increased the risk of hospitalization and mortality due to COVID-19 [30].…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional, observational follow-up for 284 COVID-19 infected persons indicated that multiple comorbidities are closely related to the severity of COVID-19 disease progression and the higher mortality rate was seen in smokers as compared with healthy patients [29]. A study on 10,713 COVID-19 patients in Espírito Santo State, Brazil, reported that older age, male gender, Asian, indigenous or unknown race, comorbidities like smoking, kidney disease, obesity, pulmonary disease, diabetes, and cardiovascular disease, as well as fever and shortness of breath, increased the risk of hospitalization and mortality due to COVID-19 [30].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of diabetes related complications (such as cardiovascular and renal complications, neuropathy, blindness, etc.) [50] may increase during the pandemic as a result of uncontrolled diabetes, requiring further care for individuals. Major changes have already been observed in the healthcare systems which interrupt existing best practices that have been set up to reduce the risk of diabetic related complications [45].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in an observational study conducted in Croatia, it was reported that women who smoked a greater number of cigarettes had a lower frequency and duration of PA than men and were more likely to gain weight, factors that influence a decrease in quality of life [45]. On the other hand, the presence of comorbidity is closely related to the severity and progression of the COVID-19 disease and higher mortality; there is a higher mortality rate in smoking subjects compared to healthy subjects; however, the presence of some comorbidities (e.g., diabetes) and diabetes + smoking increases the risk of mortality through COVID-19 [46]. Therefore, it is essential to maintain optimal levels of PA, because they may be protective elements for health [12][13][14].…”
Section: Discussionmentioning
confidence: 99%